The impact of digital learning resources, teacher support, and peer collaboration on academic performance of vocational and technical college students in China - Zhu, Yan; Fu, Shengqi; Lee, Shiou Yih; Kong, Hong (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigated the impact of digital learning resources, teacher support, and peer collaboration on academic performance among vocational and technical college students in China. Adopting a quantitative descriptive-correlational study design, data were collected from 760 students across three vocational colleges in Shenzhen, Guangdong Province, China. Data were statistically analyzed through SPSS 26.0, employing correlation and multiple regression analyses. Correlation results indicated strong positive correlations between all of the variables and academic performance as follows: digital learning resources, teacher support, and peer collaboration. The regression model explained 46.2% of the explained variation of academic performance, and teacher support was the most significant predictor, followed by digital learning resources and peer collaboration. Results confirm an integrative theoretical framework of Social Cognitive Theory, Technology Acceptance Model, and Social Learning Theory. The study depicts that the effectiveness of vocational education entails holistic measures combining technological advancement, extensive teacher support and collaborative learning opportunities. The findings provide evidence-based implications for education administrators and policymakers to facilitate student success strategically through resource allocation and enhancement of teaching methodologies.